Penerapan Sistem Self Assesment Pada Bea Perolehan Hak Atas Tanah Dan Bangunan ( BPHTP) Oleh Wajib Pajak Untuk Menentukan Pajak Terhutang - Djatmiko, S.H., M.H., Agoes; Hartariningsih, S.H., M.H., Ninik; Hariadi, S.H., M.Hum., Wahyu (Cakrawala Hukum, 2014)
This study uses a method used is the method of normative juridical approach . Research the law that contain legitis - positivist conception , which profound that the law is identical to the written norms are created and legislated by agencies / officials authorized state made ââwritten and promulgated by agencies or officials of the state. This conception of law as a sisitem see normative autonomous , closed and regardless of peoples lives . This study uses the specification of legal discovery research in concreto , in an attempt to discover whether the appropriate law to be applied , in order to solve a particular case where the rule of law and it can diketemukan.Selain it also has the objective to test whether a particular normative postulates it may or may not used to solve a specific legal problem . Source of data needed in this study is a secondary data source which secondary data required in this study consists of the following: a . Primary legal materials are materials - materials that form a binding legal regulations - regulations in the field of taxation . b . Secondary legal materials are materials - materials that explain the law of primary legal materials consisting of books , journals , and papers - papers relating to tax matters Methode Data Collection , Data needed in research , collected by way of literature , namely explore the literature and other reference sources available in the library or elsewhere Keywords : Self Assessment , Dty Acquisition Right up Lang and Building , Assessable , tax due